Leaf and flower essential oil compositions of Gliricidia sepium (Fabaceae) from Costa Rica - Chaverri Chaverri, Carlos (2015)
Gliricidia is a small genus of flowering plants in the Fabaceae family. Gliricidia sepium is a multipurpose tree native to Mesoamerica and possibly northern South America. The chemical composition of the hydrodistilled essential oils of G. sepium, growing wild in the Central Pacific coast of Costa Rica, was analyzed by capillary gas chromatography-flame ionization detector (GC-FID) and capillary gas chromatography-mass spectrometry (GC-MS) using the retention indices on DB-5 type capillary column. A total of 96 and 109 compounds were identified in the leaf and flower oils, respectively, corresponding to 87.9% and 89.2% of the total amount of the oils. The leaf oil consisted mainly of aliphatics (54.9%) and terpenoids (28.1%). The major compounds from the leaf oil were pentadecanal (18.7%), (Z)-phytol (7.8%), methyl linolenate (6.0%) and nonanal (5.1%). The flower oil consisted mainly of aliphatics (58.9%) and terpenoids (25.8%). The major components of the flower oil were hexadecanoic acid (19.7%), myrtenol (7.7%) and (E)-nerolidol (5.9%).